Impact of Loan Interest Rate on Performance of Small and Medium Enterprises a Case Study of Rosika Company Limited in Kabale Municipality. - Twongyeirwe, Sonia (Kabale University, 2024)
The study examined the impact of loan interest rates on the performance of small and medium enterprises (SMEs), focusing on Rosika Company Limited in Kabale Municipality. The objectives were to identify the loan interest rates applied by financial institutions to SMEs, assess the performance levels of SMEs, and explore the relationship between loan interest rates and SME performance. A cross-sectional survey design was employed, with data collected through interviews and questionnaires. Regarding the roles of loan interest rates, most respondents indicated that favorable interest rates enhance operational efficiency, boosting performance and profitability. Fewer respondents noted that favorable rates help SMEs cover costs and sustain normal operations, ultimately achieving profits. Concerning the performance levels of SMEs, the majority cited increased sales volumes as the primary indicator, while fewer respondents highlighted efficiency in generating profits from assets. On the relationship between loan interest rates and SME performance, most respondents agreed that favorable interest rates promote borrowing, expand the capital base, and increase business activity. A smaller proportion stated that lower interest rates reduce interest costs, enhancing SME performance. The study recommended extensive sensitization and guidance for SME owners on effectively utilizing loan funds from financial institutions. This would enable them to repay loans successfully while maximizing the benefits derived from borrowed funds.